(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
Interventions using Applied Behavior Analysis (ABA) are one of the main evidence-based interventions proved to be effective for individuals with autism. The Discrete Trial Teaching (DTT) is widely used in the treatment of autism and its training is often required for its implementation. The present study reviewed the literature about training procedures with video modeling (VM) for teaching professionals and paraprofessionals to implement DTT. The terms “video modeling” and “discrete trial” were combined with the terms “staff training”, “parent training” or “caregiver training”, generating three combination sets which were used in PubMed, Scielo, Redalyc, and LILACS databases. After applying inclusion and exclusion criteria, seven studies were selected and analyzed according to five categories. The results showed that VM is effective and has a great potential to be widely used as a low-cost training tool.